Analysis of Factors Affecting the Performance of Midwives in Completing the E-Cohort - Dini Herza Magfurotin; Sunanto; Iis Hanifah (KHD Production, 2023)
Performance can be seen as a process or work result. Performance is the process of how work takes place to achieve work results. This study aimed to analyze factors affecting the performance of midwives in completing the e-cohort. This research uses descriptive research with a quantitative approach. This study used a research design with a cross-sectional study. Seventeen mothers, the sample studied was 17 respondents and was taken by total sampling. Data collection included coding, editing, and tabulating; then, data were analyzed manually and by computer with the chi-square test. Based on 17 respondents, it was obtained that the p=0.033 (significance level of 0.05), which can be interpreted as accepting, so that there is an influence of knowledge on the performance of midwives. The p=0.034 is acceptable, so adaptation and flexibility affect midwife performance. The value of p=0.071 is acceptable, so accountability affects the performance of midwives. At a p=0.451, it is acceptable that communication skills influence midwives' performance. Based on the cross-tabulation, nine respondents (52.9%) performed well in filling out the E-Cohort. The results obtained by x2 are greater than p, so it can be concluded that there are factors that most dominantly influence the performance of midwives in filling out the E-Cohort in the working area of ​​the Leces Health Center, Leces District, Probolinggo Regency. The results of this study can provide information and input for the Leces Health Center that the incidence of abortion is still high, so it is suggested that the midwifery polyclinic, especially midwives, can improve public health programs such as counseling and early detection of at-risk pregnancies, can play a role in efforts to improve the quality of midwifery services by participating in the program.